Molecular biomarkers of progression from Barrett’s esophagus to esophageal adenocarcinoma - Taylor, Luke; Alastal, Hani Naeem; Rasheed, Ashraf (Frontiers in Gastroenterology, 2023)
Introduction Barrett's oesophagus (BO) is a pre-malignant condition for oesophageal adenocarcinoma (OAC), the incidence rate of which has been rising dramatically over the last four decades in the western world. 5-year Survival of OAC is poor, and one of the ways to improve this would be by focusing on identifying high-risk Barrett's patients through a surveillance program. Currently, histological dysplasia is the only recognized marker of progression to OAC. Molecular biomarkers found in tissue samples may act as a reliable tool for the stratification of patients with BO, based on risk of progression. Methods Immunohistochemistry was performed on 25 tissue samples obtained from endoscopic biopsy of 19 patients with confirmed BO. H&E staining was used to confirm presence of BO and dysplasia. Staining was performed by an external independent laboratory. Statistical analysis using the Mann-Whitney U test was performed using R Studio® statistical software. Results Of the 19 patients sampled, 3 had low grade dysplasia and all had confirmed metaplasia diagnostic of BO. Expression of Cyclin D1 was noted to be elevated in patients with low-grade dysplasia (LGD) when compared with metaplasia only, p = 0.042. Expression of Sox 2 was elevated in metaplastic BO cells within the stain compared with normal squamous cells within the same stain, p = 0.046. Of all eight biomarkers tested, b-Catenin had the greatest overall expression, p<0.004. Conclusions Isolating elevated Cyclin D1 in patients with LGD highlights its potential as a biomarker in identifying BO patients at risk of developing dysplasia and furthermore possible progression to OAC. The elevated levels of Sox 2 and b-Catenin may also serve as markers for disease progression when over-expressed in BO patients. Both conclusions, however, would need long term follow up to fully establish their prognostic usefulness, as at time of writing, no patients in this study had gone on to develop OAC. Although only a small sample size was present for this study, and follow up was limited, it serves as a strong pilot for further research into the use of novel biomarkers in predicting high risk BO patients for development of dysplasia and progression to OAC.